2010
DOI: 10.1111/j.1365-2486.2009.02076.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of six European tree species and land‐use legacy for nitrogen and water budgets in forests

Abstract: Water and nutrient fluxes for single stands of different tree species have been reported in numerous studies, but comparative studies of nutrient and hydrological budgets of common European deciduous tree species are rare. Annual fluxes of water and inorganic nitrogen (N) were established in a 30-year-old common garden design with stands of common ash (Fraxinus excelsior), European beech (Fagus sylvatica L.), pedunculate oak (Quercus robur), small-leaved lime (Tilia cordata Mill.), sycamore maple (Acer pseudop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…This difference in water flux is related to differences in leaf area, which has a large influence on transpiration and interception loss and was greatest for spruce. Low water flux under spruce stands is also in accordance with other Scandinavian studies (Christiansen et al 2006(Christiansen et al , 2010. The relative difference in DOC flux from the O horizon between tree species was thus lower than the relative difference in concentrations from the same horizon, but there were still larger fluxes from the coniferous stands compared to the birch stands.…”
Section: Discussionsupporting
confidence: 91%
“…This difference in water flux is related to differences in leaf area, which has a large influence on transpiration and interception loss and was greatest for spruce. Low water flux under spruce stands is also in accordance with other Scandinavian studies (Christiansen et al 2006(Christiansen et al , 2010. The relative difference in DOC flux from the O horizon between tree species was thus lower than the relative difference in concentrations from the same horizon, but there were still larger fluxes from the coniferous stands compared to the birch stands.…”
Section: Discussionsupporting
confidence: 91%
“…We combined existing data on various leaf litter quality characteristics and forest floor turnover rates with new data on soil biogeochemistry and earthworm communities to broaden the understanding of plant-soil interactions in this well-studied common garden experiment [35][36][37]. We found that total earthworm biomass in Fraxinus, Acer and Tilia stands was, on average, two times higher than in Quercus and Fagus stands and eight to ten times higher than in Picea stands.…”
Section: Discussionmentioning
confidence: 98%
“…We used a 36-year-old common garden experiment with sites distributed across Denmark to verify how the identity of tree species results in very different earthworm community assemblages. This replicated common garden experiment has previously revealed tree species effects on C and N stocks in the forest floor and mineral soil [35], soil respiration and soil organic C turnover [36] and on N cycling and leaching and the water budget [37]. We aim to broaden the understanding of plant-soil interactions in this common garden experiment by combining existing data on various litter quality characteristics and forest floor turnover rate with new data on soil biogeochemistry and earthworm communities.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, bioturbation has been identified as a key factor controlling the incorporation of SOC into the mineral soil (Vande Walle et al 2001) through the transformation of litter into fecal matter and the transport into deeper mineral soil horizons by endogeic earthworm species (Marhan and Scheu 2006). Moreover, the general higher packing of Norway spruce stands can intercept higher amount of solar radiation and rainfall (Christiansen et al 2010), which can further slowdown decomposition through diminishing the activity of soil biota.…”
Section: Discussionmentioning
confidence: 99%